(untitled) (Comprehensive Journal of Science, 2026)
Rice is one of the most widely consumed foods around the world. It is often prepared in large quantities and stored for later consumption, which makes it susceptible to bacterial contamination, particularly by Bacillus cereus. This bacterium is capable of producing toxins that lead to severe food poisoning. It thrives in starchy foods like rice and can form heat-resistant spores that survive conventional cooking. These spores can then germinate and multiply under improper storage conditions, especially at room temperature. This study aimed to detect the presence of Bacillus cereus in cooked rice stored at different temperatures (room temperature, refrigeration, and freezing), and to analyze the impact of storage and reheating on its survival and activity, in order to assess the potential food safety risks associated with these practices. Laboratory experiments were conducted on cooked rice samples stored for specific time periods. Bacterial growth was evaluated using selective media, and changes in pH and odor were analyzed. The effect of reheating on reducing bacterial counts was also examined. The results showed that storing rice at room temperature for extended periods significantly increased the numbers of Bacillus cereus, posing a potential health risk to consumers. Refrigeration and freezing helped reduce bacterial growth but did not eliminate it entirely. It was found that inadequate reheating does not completely eliminate the bacterial threat, especially when rice is reheated multiple times. Sensory observations indicated a slight correlation between odor changes and bacterial contamination; however, some contaminated samples showed no clear sensory signs. This study highlights the importance of controlling storage temperatures and reheating practices for starchy foods, particularly in home and restaurant settings, to reduce the risk of foodborne illness caused by Bacillus cereus. It also recommends public awareness campaigns and urges health authorities to establish strict guidelines regarding the storage and reheating of cooked foods.